IMPORTANCE OF USE OF MODERN INFORMATION TECHNOLOGIES IN THE PRESCHOOL EDUCATION SYSTEM (Scientific journal of the Fergana State University, 2024)
Raising a child is a very complex and responsible process. The correct and effective organization of this process remains a pressing task in every era. Especially in today’s time of acceleration and various innovations, the introduction of information and communication technologies and innovations into the education system effectively helps solve this problem. This article describes the scientific and practical aspects of introducing ICT and innovation into the preschool education system, as well as its effective results.